Exploring Women’s Multi-Level Career Prospects in Pakistan: Barriers, Interventions, and Outcomes - Sarwar, Ambreen; Imran, Muhammad Kashif (Frontiers in Psychology, 2019)
Abstract Utilizing the relational framework of diversity management and social role theory, this exploratory study illuminates the career prospects of women working in patriarchal society of Pakistan. With the help of Nvivo 12 Plus, themes were generated based on 27 in depth, semi-structured interviews. The findings showed interrelated web of factors interacting at three levels; macro, meso and micro; that were explained in the premises of social role theory. Major impediments to women’s career progress were religious interpretations, socio-cultural factors and Sifarish (i.e. favoritism/ nepotism) at the macro-level. At the meso-level, the barriers involved segregation, discrimination, harassment and lack of work-family balance initiatives at workplace. The micro-level obstacles involved personal values and needs, queen bee syndrome and lack of awareness. The experiences of Pakistani women varied based on socio-economic status, marriage, religion and various aspects of individual identity, that intersected with gender and accordingly affected their career outcomes either positively or negatively. Therefore, the study also contributes to the emergent area of intersectional studies which posits that individuals experience various facets of identity concurrently and that these factors do not operate separately but are interrelated and interact. Moreover, the study also highlighted the interventions for creating gender parity like clarification of Islamic guidelines, strict accountability of workplace policies, and provision of work-family balance support. The outcomes highlighted by the respondents included happiness, confidence, agency, and improved quality of life. The paper concludes with implications for theory and practice, limitations and future research avenues.